Arquitetônica social escolar: um estudo sócio, histórico e cultural sobre as relações de poder e controle nos espaços, artefatos e discursos - Tanzi Neto, Adolfo (2016)
This doctoral thesis, situated in the field of Applied Linguistics, seeks to address the role of language in different school settings. Through the study of three distinct schools of the Brazilian public education, a more traditional one, another full-time with experimental involvement projects with students and the last one with democratic principles without walls, classes, grading or classification. The present research pursues to answer how the relations of power and control in social positions and discursive mediation artefacts constitute a specific school space and thus, influence the conscience formation of its participants. The research also investigates how a school space, and its relationship with a distinct physical space, contributes to different possibilities of social positions of psychological tools and discursive artefacts. Therefore, based on a socio historical cultural research, exploring the concept of mediation [oposredovanie] Vygotsky (1978, 1981, 1987, 2009 [1934]), we seek to understand how the human cultural development is being performed and how participants of this culture are mutually shaped, for being social, cultural and institutionally situated. From the reflections of Bakhtin (2010 [1924]) and Bernstein (2003 [1990], 1996, 1999, 2000) other aspects are analysed. The first author bolsters this research with studies on the architectonic form, aesthetic and genre, in which we attempt to understand the verbal-visual mass of an architectonic whole and thus, understand their interdependencies, its dialogical and axiological positions in architectonic form that governs the construction of a verbal-visual mass. The second contributed with studies on the relations of power and control within an institution that tend to govern the forms of communication or open spaces for different forms of communication to be materialised. This research indicated that it is possible to break the boundaries of power and control, discourses and regulatory practices of more traditional physical and social school spaces and therefore, break the invisible barriers, offering a more horizontal space of social positions, exchange, identities and voices of its participants. In this sense, we believe that it is possible to reconfigure the architectonic form of any physical and social space in order to propose different relationships between agents, hierarchical rules etc. To this end, we note the importance of the verbal-visual productions in different school spaces, which favoured the voice of the student, reconfiguring their dialogic and axiological positions in the architectonic form of the school social space. Thus, even in a more traditional organizational and pedagogical space context, we found that the social basis, the voice and identity of students, when privileged, generated a school closer to students, which engendered feelings of belonging and school recognition relationship as a change agent for achievement of future dreams